2000
DOI: 10.1039/b000739k
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) complexes of the isomeric tetraazamacrocyclic ligands 1,11- and 1,8-bis(2-pyridylmethyl)-1,4,8,11-tetraazacyclotetradecane and of the 1,4,8,11-tetraazacyclotetradecane-5,12-dione analogue at neutral and basic pH

Abstract: Copper(II) complexes of the isomeric tetraazamacrocyclic ligands 1,11-and 1,8-bis(2-pyridylmethyl)-1,4,8,11-tetraazacyclotetradecane and of the 1,4,8,11-tetraazacyclotetradecane-5,12-dione analogue at neutral and basic pH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 15 publications
(13 reference statements)
4
45
0
Order By: Relevance
“…methanol does not affect the shape nor the position of the absorption band. The electronic spectrum of cyclam-Cu complex in a square-planar form [71][72][73][74] or distorted-octahedral geometry exhibits a quite broad absorption band between 540 and 600 nm, as it is shown in Fig. 10.…”
Section: Cyclam-copper Moleculesmentioning
confidence: 81%
“…methanol does not affect the shape nor the position of the absorption band. The electronic spectrum of cyclam-Cu complex in a square-planar form [71][72][73][74] or distorted-octahedral geometry exhibits a quite broad absorption band between 540 and 600 nm, as it is shown in Fig. 10.…”
Section: Cyclam-copper Moleculesmentioning
confidence: 81%
“…Cyclam [62] constitutes a useful building block for the creation of porous hybrid systems, since it results in a scaffold possessing four polycondensation directions with a central cavity able to coordinate transition-metal ions. The various topologies of the ligands lead to a wide variety of coordination modes with metal centers; examples of these are square-planar, square-pyramidal, [60,[63][64][65][66] and octahedral coordination geometry, and square antiprism polyhedra, [59,[67][68][69] depending on the number and the nature of the coordinating arms anchored to the macrocycle and the stereochemical constraints. The incorporation of tetraazamacrocycles in a material should yield stabilization of unusual metal coordination stereochemistries and reactivity of the complexes.…”
Section: -Peroxodicopper(ii) and Bisa C H T U N G T R E N N U N G (M-mentioning
confidence: 99%
“…[12][13][14] On the other hand, L 9 forms a five-coordinate complex in which one of the pyridyl groups is not involved in the coordination. 15 It has been also reported that L 2 reacts with Cu 2+ ion more slowly than does the unsubstituted macrocycle L 1 . 12 This observation contradicts those reported for other 14-membered tetraaza macrocycles bearing two or four 2-hydroxyethyl pendant arms.…”
Section: -15mentioning
confidence: 96%
“…Although L 2 , L 8 , and L 9 bearing two N-(2-pyridylmethyl) groups typically form mononuclear complexes, the fully N-substituted macrocycle L 7 acts as a binucleating ligand. 8,9,[12][13][14][15] The two pyridyl groups in [CuL 2 ] 2+ or [CuL 8 ] 2+ are coordinated to the metal ion. [12][13][14] On the other hand, L 9 forms a five-coordinate complex in which one of the pyridyl groups is not involved in the coordination.…”
Section: -15mentioning
confidence: 99%
See 1 more Smart Citation